THE EFFECT OF AN INTENSIVE ENGLISH COURSE ON STUDENTS’ SPEAKING SKILL IN HIGHER EDUCATION - Nur Aini, Devi (International Journal of Multidisciplinary Reseach, 2025)
English speaking skill is important for an English learner. Students as English learners also do variative activities to improve it. The purpose of this study was to investigate the effect of an intensive English course on students’ speaking skill development. Using a quantitative research design, the study examined the improvement in students’ speaking performance before and after participation in a six-week intensive English program. A total of 51 undergraduate students were selected through purposive sampling and assessed using a standardized speaking proficiency test. Pre-test and post-test scores were analysed using descriptive statistics and paired sample t-tests to determine the significance of the observed differences. The findings revealed a statistically significant improvement in students’ speaking skills after completing the intensive course, particularly in fluency, pronunciation, and vocabulary use. The results suggest that intensive English instruction provides an effective approach for enhancing oral communication skills within a relatively short period. Based on these findings, the study recommends that language institutions and universities integrate intensive English programs as a complementary strategy to regular language instruction to promote more rapid speaking proficiency development.